Transformasi Sistem Rekognisi Pembelajaran Lampau (RPL) di Lingkungan Kampus melalui Penguatan Asesor dan Tata Kelola - Sarumaha, Yenny Anggreini (CV. Kurnia Grup, 2026)
The implementation of Recognition of Prior Learning (RPL) is a crucial strategy for higher education institutions to enhance educational accessibility for practitioners and experienced individuals. This community service activity was initiated by the Quality Assurance Instritute (LPM) of Universitas Cokroaminoto of Yogyakarta (UCY) with the aim of socializing RPL policies and strenghthening the institution’s internal governance. The methods employed included Focus Group Discussions (FGD), workshops for developing assessment instruments and cross-unit coordination involving faculty leaders, study programs, and the stude affairs/admission department. The results indicate a significant increase in leadership understanding regarding the urgency of RPL. Furthermore, the activity successfully established an efficient registration workflow between admission department and study programs, as well as formulated objective portofolio assessment instruments aligned with quality standards. The resulting sustainability strategies include the digitalization of recognition documents and the strengthening of assessor legality through Rector’s Decress. The conclusion of this activity is UCY’s systemic readiness to implement an accountable and quality-orientes RPL pathway.